Spiritual Leadership Scale: Theoretical Foundations and Empirical Validation in the Context of Turkish Employees - Okan, Yusuf Taha; Okan, Nesrullah (Springer, 2024)
The objective of this study was twofold: firstly, to develop a novel scale for measuring the concept of spiritual leadership, and secondly, to evaluate the psychometric properties of this scale. The principal objective was to facilitate the assessment of spiritual leadership on the part of managerial personnel. In the course of the research, a three-stage process was undertaken. In the initial phase, the theoretical underpinnings of the concept were established through a comprehensive review of the spiritual leadership literature, and an item pool was constructed. In the second stage, exploratory factor analysis (EFA) was employed to ascertain the factor structure of the scale. In the third stage, confirmatory factor analysis (CFA) was employed to corroborate the identified structure and criterion validity analysis was conducted. The EFA results indicated that the scale exhibited a single-factor structure. The CFA results demonstrated that the model exhibited good fit indices, thereby confirming the single-factor structure. In the reliability analyses, the internal consistency coefficient (Cronbach's alpha) of the scale was 0.988, which indicated a high level of reliability. These findings collectively demonstrate that the spiritual leadership scale possesses sufficient validity and reliability.
Keywords: Spiritual leadership; Scale development; Employees; Validity; Reliability